Conservation of ‘Palmer’ mango with an edible coating of hydroxypropyl methylcellulose and beeswax - Sousa, Fagner F. [UNESP]; Pinsetta Junior, José S. [UNESP]; Oliveira, Karollayne T.E.F. [UNESP]; Rodrigues, Ellen C.N. [UNESP]; Andrade, Josiele P.; Mattiuz, Ben-Hur [UNESP] (Elsevier, 2021)
Mango is a tropical fruit presenting intense postharvest metabolism. In storage at room temperature, it presents a short shelf life due to the high respiratory rate, and consequent ripening, which limits the marketing period in distant regions. This study evaluated the effect of edible coatings of hydroxypropyl methylcellulose and beeswax in concentrations of 10, 20, and 40% in ‘Palmer’ mangoes stored for 15 days at 21 °C. The coatings controlled ripening, maintaining peel and pulp colors, firmness, soluble solids (SS), titratable acidity (TA), SS/TA ratio, sugars, ascorbic acid, phenolic compounds, flavonoids, β-carotene, and antioxidant activity. Also, they reduced weight loss, oxidative stress, and the anthracnose (Colletotrichum gloeosporioides) incidence, without inducing alcohol dehydrogenase activity, which suggests that coated fruit did not ferment. Treatment with 20% beeswax was the most suitable for industrial applications, increasing in six days the mangoes shelf life.
Keywords: Biopolymer; HPMC; Hypromellose; Mangifera indica; Natural products; Postharvest